Ekstraksi Zat Warna Alami Dari Kulit Batang Jamblang (Syzygium cumini) Sebagai Bahan Dasar Pewarna Tekstil - Mukhlis Mukhlis (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2011)
Has done research on the extraction of natural pigments from bark of Jamblang (Syzygium cumini) as a base for textile dyes. This study aims to extract natural dyes from bark of  Jamblang as the base material of textile dyes. The research was conducted in the laboratory of Chemistry FKIP Syiah Kuala University. The population in this study is Jamblang bark (Syzygium cumini) in Ujung Batee, Aceh Besar as much as 3 kg. A total of 500 gram sample of wet bark of jamblang sokhletasi extracted with 2500 ml of water. Water extract was concentrated by evaporator and the viscous extract obtained as many as 77.984 grams. Confirmation test results of water condensed tannins in the bark extract showed a positive presence jamblang hydrolyzed tannins. Viscous extract obtained water test conducted on fabric dyeing, paper, and wood. Dyeing process is done by soaking for 1 hour at a temperature of 100oC and followed by a fixation on the fabric color by using FeSO4, alum, and potassium bichromate for 15 minutes. Dyeing with bark extract of Jamblang give good results on fabric and paper, whereas the only stain on the wood surface is uneven. The results of dyeing the cloth with a fixation process to vary the color and fastness is good.